H(2)S mediates O(2) sensing in the carotid body - Peng, Ying-Jie (National Academy of Sciences, 2010)
Gaseous messengers, nitric oxide and carbon monoxide, have been implicated in O(2) sensing by the carotid body, a sensory organ that monitors arterial blood O(2) levels and stimulates breathing in response to hypoxia. We now show that hydrogen sulfide (H(2)S) is a physiologic gasotransmitter of the carotid body, enhancing its sensory response to hypoxia. Glomus cells, the site of O(2) sensing in the carotid body, express cystathionine γ-lyase (CSE), an H(2)S-generating enzyme, with hypoxia increasing H(2)S generation in a stimulus-dependent manner. Mice with genetic deletion of CSE display severely impaired carotid body response and ventilatory stimulation to hypoxia, as well as a loss of hypoxia-evoked H(2)S generation. Pharmacologic inhibition of CSE elicits a similar phenotype in mice and rats. Hypoxia-evoked H(2)S generation in the carotid body seems to require interaction of CSE with hemeoxygenase-2, which generates carbon monoxide. CSE is also expressed in neonatal adrenal medullary chromaffin cells of rats and mice whose hypoxia-evoked catecholamine secretion is greatly attenuated by CSE inhibitors and in CSE knockout mice.